Extension of the Periods for Payment of Quota Increases Under the Fourteenth General Review of Quotas and the 2008 Reform. (Policy Papers; Policy Paper ;, 2016)
This paper proposes a further 30-day extension of the period for payments of quota increases under the Fourteenth General Review of Quotas ('Fourteenth Review'), and an extension for the payment of the quota increases under the 2008 Reform, through April 27, 2016.